TAWARAN METODE OTENTIFIKASI DAN PEMAHAMAN HADIS MUHAMMAD SYUHUDI ISMAIL - fauzi, fauzi; Indah Nur Fadila (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2025)
The study of proposed methods for the authentication and understanding of hadith is important to discuss, as in the early 14th century Hijri, many Orientalists had obscured the existence of the Prophet's hadith. The aim of this study is to analyze the proposed methods of hadith authentication and understanding according to Syuhudi Ismail. This research uses a library research method. The sources of this study are books authored by Syuhudi Ismail and relevant articles. The analytical method employed in this article is content analysis. The results of the study show that: (1) a hadith can serve as a strong argument if it fulfills the criteria of authenticity, both in terms of its chain of transmission (sanad) and content (matan); (2) the method of hadith criticism used by Syuhudi Ismail is based on the principles of authenticity in sanad and matan, which have been simplified into major and minor principles; (3) the principles for understanding hadith content can be applied both textually and contextually, taking into account universal, temporal, and local values or teachings.